Chitosan coating effect on storability and quality of grapes (vitis vinifera l.) / Alyaa Nadzirah Mohd Shukri - Mohd Shukri, Alyaa Nadzirah (Faculty of Applied Sciences, 2017)
Chitosan is known for their ability in forming a semi-permeable membrane, and proved to be a safe product. Chitosan also widely used due to their potential to inhibit any microbial growth. The aims of this experiment are to study the effectiveness of chitosan coating on storage life of Vitis vinifera L. and to compare the condition of V vinifera L. coated with chitosan under two different temperatures. The results of this study showed that chitosan coating are really effective to control the weight loss and to control the development of fungal decay of V vinifera L. especially during storage at 4 °C, compared to 28 °C (room temperature). The percentage of weight loss and percentage of development of fungal decay of V vinifera L. increased when the concentration of chitosan decreased at 4 °C, however at 28 °C, chitosan solution 1.0% showed the best result in the control of fungal decay and control of weight loss. Therefore, chitosan coating method are important to prolong the storage life of fresh fruit, and suggestable to store at refrigerated temperature with high chitosan concentration.